THE EFFECT OF SELF -TALK STRATEGY ON STUDENTS SPEAKING ABILITY FOR ELEVENTH GRADE OF SMK SWASTA SWAKARYA SALAPIAN - Ayu Indari; Sri Meriahna Surbakti (VISION, 2022)
The purpose of this research is to know the effect of Self Talk Strategy on students’ speaking ability in academic year 2021\2022.  The type of this research is quasi experimental group. It is a research to know that the effect between two variables, there are dependent variable is using Self Talk Strategy and independent variable is students’ speaking ability. This research was done at Smk Swasta Swakarya Salapian in academic year 2021\2022. The population of this research was three classes the total of the students was 88 students. Sample of the research was taken by two classes, for experimental class and control class. Based on the data, the result of   in significance 5%, result  was 1,029 > 0, 3365 it means that there was a significance effect between Self Talk Strategy to the students’ speaking ability in eleventh grade of Smk Swasta Swakarya Salapian in academic year 2021\2022.